1988
DOI: 10.1103/physreva.38.2991
|View full text |Cite
|
Sign up to set email alerts
|

Some parametric instabilities of an ordinary electromagnetic wave in magnetized plasmas

Abstract: Some of the parametric instabilities of an ordinary electromagnetic wave decaying into (i) a highfrequency upper hybrid wave and a low-frequency mixed-mode kinetic Alfven wave and (ii) an obliquely propagating ordinary scattered electromagnetic wave and a low-frequency electrostatic-ion Bernstein wave (stimulated Brillouin scattering) have been investigated. In channel (i), the partially electrostatic nature of the kinetic Alfven wave and the component of the low-frequency ponderomotive force along the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Recently, the works further point out that the KAWs can parametrically excite the convective cell [ Pokhotelov et al , 2003; Onishchenko et al , 2004]. On the other hand, the KAWs can also be excited by other modes, such as by the whistler wave [ Chen , 1977; Sharma et al , 1986], the lower hybrid wave [ Shukla and Mamedow , 1978], the high‐frequency radio wave [ Papadopoulos et al , 1982], the ion cyclotron wave [ Yu et al , 1984; Patel et al , 1985], the ion Bernstein wave [ Sharma and Tripathi , 1988], the ordinary electromagnetic wave [ Triphthi and Sharma , 1988], the higher hybrid wave [ Yukhimuk et al , 1998], the Langmuir wave [ Voitenko et al , 2003], and MHD waves [ Voitenko and Goossens , 2002, 2005a, 2005b; Fedun et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the works further point out that the KAWs can parametrically excite the convective cell [ Pokhotelov et al , 2003; Onishchenko et al , 2004]. On the other hand, the KAWs can also be excited by other modes, such as by the whistler wave [ Chen , 1977; Sharma et al , 1986], the lower hybrid wave [ Shukla and Mamedow , 1978], the high‐frequency radio wave [ Papadopoulos et al , 1982], the ion cyclotron wave [ Yu et al , 1984; Patel et al , 1985], the ion Bernstein wave [ Sharma and Tripathi , 1988], the ordinary electromagnetic wave [ Triphthi and Sharma , 1988], the higher hybrid wave [ Yukhimuk et al , 1998], the Langmuir wave [ Voitenko et al , 2003], and MHD waves [ Voitenko and Goossens , 2002, 2005a, 2005b; Fedun et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper ion heating in connection with parametric decay at the beat frequency has been discussed and explained analytically as heating by parametrically excited low-frequency ion-Bernstein waves (Tripathi & Sharma 1988) in a multi-ion-species plasma (Dash, Sharma & Buti 1984;Sharma, Yashvir & Bhatnagar 1986;Milic & Krstic 1987). It has been found that the growth rate can be controlled by several parameters, such as the mass, density and temperature of two ion species.…”
Section: Discussionmentioning
confidence: 99%
“…a high-frequency lower-hybrid wave and a low-frequency ion-Bernstein wave in a multi-ion-species plasma. Parametric decays are among the most promising heating mechanisms for plasmas (Porkolab & Chang 1977;Tripathi & Sharma 1988). The idea of heating by parametric decay is to pump power into modes at technically available frequencies; the pump modes themselves are not effectively absorbed by the plasmas, but one or both of the decay modes are (Krause, Luthen & Schluter 1980).…”
Section: Introductionmentioning
confidence: 99%